The Influence Of Work Environment And Service Quality Service To Employee Performance At Cv. Prasetio Adijaya Group In Bandar Lampung - Prasetio, Rizki Lazuardi; Junaidi, Junaidi (Universitas Dehasen Bengkulu, 2025)
The object of this research is employees of the CV.Prastio Adijaya Group in Bandar Lampung. This research aims to determine the influence of the work environment and service quality on the performance of employees of the CV.Prastio Adiwijaya Group in Bandar Lampung. This research used a survey via a questionnaire in the form of a statement which assessed the respondent's level of agreement with a Likert scale of 1 to 5, distributed to 27 respondents consisting of employees of the CV.Prastio Adiwijaya Group in Bandar Lampung. The total influence of the Work Environment and Service Quality on Employee Performance is 94.7% and the remaining 5.3% is due to other factors which the author did not examine in writing this thesis. Based on the table above, a regression model can be created in which the influence of work environment variables and service quality together (simultaneously) has a positive effect on employee performance, which can be seen from the calculated F value of 50,854, much greater than the F table value with a significance of 0.05, which is 3.403 with The significant value of 0.00 is smaller than 0.05. This shows that together the work environment and service quality have a positive and significant effect on the performance of CV.Prastio Adijaya Group employees in Bandar Lampung.